Method for improving hardness of diamond particles through mosaic splicing
Through mosaic splicing technology and CVD deposition process, multi-layer structure diamond particles are formed, solving the problem of improving the hardness and uniformity of diamond particles in the existing technology, and achieving efficient performance improvement of diamond wire saws and rope saws, suitable for high-precision cutting tool.
Patent Information
- Application Number
- CN202411279351.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-12
AI Technical Summary
In the preparation of diamond particles, it is difficult to achieve both hardness and uniformity while improving, and high temperature and high pressure annealing and CVD methods have equipment limitations and high costs, making it difficult to achieve ideal doping effects and multi-layer structures.
Through mosaic splicing technology, undoped single crystal diamond particles are spliced onto a copper substrate, and the doped diamond layer is pulsed by CVD technology, and combined with the alloy powder to form a multi-layer structure through hydrogen etching and acid etching treatment. diamond particles.
It significantly improves the hardness and toughness of diamond particles, simplifies the process flow, reduces production costs, is suitable for high-precision cutting and processing applications, and improves the cutting efficiency and service life of diamond wire saws and rope saws.
Smart Images

Figure CN119265534A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of superhard material preparation, and in particular relates to a method for improving the hardness of diamond particles through mosaic splicing. Background Art
[0002] Diamond particles are widely used in the industrial field due to their ultra-high hardness and excellent wear resistance, especially in high-precision cutting tools such as diamond wire saws and rope saws. The high hardness and wear resistance of diamond particles significantly improve cutting efficiency and processing accuracy. However, diamond particles prepared by existing technologies have certain limitations in hardness and uniformity. Traditional preparation methods mainly include high-temperature and high-pressure synthesis and chemical vapor deposition (CVD). Although these methods can produce diamond particles with high hardness, the mechanical properties in practical applications are unstable due to the difficulty in accurately controlling the particle size and morphology, which affects the service life and processing effect of the cutting tool.
[0003] In the existing technology, it is difficult to form a multilayer structure with a single deposition method. Diamond particles often produce a lot of internal stress and defects during the deposition process, which reduce the overall performance of the particles. Researchers have proposed an improved method of introducing doping elements (such as nitrogen, boron, argon, etc.) into the diamond structure through doping technology to enhance its mechanical properties. However, these methods still have some challenges in practical applications, such as poor doping uniformity, complex processes, and high costs.
[0004] In addition, although the existing high temperature and high pressure annealing treatment can improve the toughness of single crystal diamond, it is difficult to achieve large-scale industrial application due to the limitations of equipment and process conditions. The existing CVD method also has similar limitations, making it difficult to achieve ideal doping effects and multilayer structures in diamond particles, further limiting the performance improvement of diamond wire saws and rope saws. Summary of the invention
[0005] In view of the above problems, the present invention proposes a method for improving the hardness of diamond particles by mosaic splicing. The method processes micropores in the substrate and splices undoped single crystal diamond particles onto a copper substrate, so that the diamond particles are partially embedded in the copper substrate. The doped diamond layer is pulse-deposited on the surface of the diamond particles by CVD technology. The diamond is combined with alloy powder to prepare a secondary deposition substrate, and the exposed diamond particles on the secondary deposition substrate are etched and then pulse-deposited with doped diamond again. Finally, the connected diamond film is broken and processed to finally obtain superhard diamond particles with a multilayer structure.
[0006] The diamond particles prepared by the present invention have higher hardness and toughness, significantly improve the cutting efficiency and service life of diamond wire saws and rope saws, and are suitable for various high-precision cutting and processing applications. The process is simplified, the production cost is reduced, and there is a wide range of industrial application prospects. The method effectively solves various problems in the prior art through multi-layer structure design and optimized deposition process, and provides a new solution for the preparation of high-hardness diamond particles.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for improving the hardness of diamond particles by mosaic splicing, the method comprising the following steps:
[0009] 1) Substrate preparation: Select the single crystal diamond particles to be processed, measure the particle size of the diamond particles, and then use an indenter with a size comparable to that of the diamond particles to machine fixedly arranged micropores on the surface of the copper substrate;
[0010] 2) First pulse deposition after splicing diamond particles: Splice single crystal diamond into micro-holes processed in the copper substrate, put the copper substrate with spliced diamond particles into the vapor deposition (CVD) equipment, introduce different doping gases in a pulsed manner, and pulse-deposit a layer of doped diamond on the surface of the exposed diamond particles, and connect the diamond particles to form a film through the deposited layer;
[0011] 3) Prepare secondary deposition substrate: remove the film formed by the particles of the pulsed deposited doped diamond layer and invert it on the alloy powder to combine the diamond film with the alloy powder to form an alloy substrate that wraps the diamond-doped surface; this step ensures that the pulsed deposited doped diamond layer is in full contact with the substrate, preparing for the subsequent deposition process.
[0012] 4) Pulse deposition again: Place the above substrate into the CVD equipment, first introduce hydrogen to etch the diamond particles to prevent graphitization damage to the diamond particles during the combination with the alloy powder, and then pulse-deposit doped diamond on the surface of the diamond particles until the thickness of the first pulse deposition is reached; this step is to continue pulse-deposit doped diamond on the lower surface of the diamond particles (i.e., the surface that has not been deposited before). The deposition conditions of this step are the same as those of step 2) to ensure the uniformity and consistency of the deposited layers on both sides.
[0013] 5) Crushing treatment: The diamond particles that have been connected to form a diamond film after deposition are acid-etched, and the diamond film is crushed after the metal residue on the surface of the diamond film is removed to obtain diamond particles with a deposition layer. Through this multi-layer structure design, the hardness and toughness of the diamond particles are significantly improved.
[0014] Preferably, in step 1), the single crystal diamond particles are spliced into the processed copper substrate micropores to increase the contact area between the diamond particles and the substrate. The micropore circumference spacing is less than twice the thickness of the pulsed deposited doping layer. If the spacing is too large, the doped diamond in step 2) will not be able to completely fill the gaps between the diamond particles, and the diamond particles cannot be connected into a film.
[0015] Preferably, in step 1), the particle size of the undoped diamond particles is micrometer-sized, preferably 4-8 μm, the maximum width of the micropores processed on the substrate is 4-8 μm, the hole depth is 2-4 μm, and the micropore circumference spacing is preferably <3 μm.
[0016] Preferably, in step 3), the alloy powder for preparing the secondary deposition substrate is selected from one of titanium-based alloys, nickel-based alloys, and copper-based alloys, and the melting point of the above alloy powder is lower than 1100 ° C. The process for preparing the secondary deposition substrate is vacuum hot melting. The above alloy powder is lower than the melting point of the diamond particles, and the diamond-doped surface can be wrapped by vacuum hot melting. The reason why a copper substrate is used in step 1) is that the diamond particles need to be spliced and arranged, and the surface of the diamond particles is relatively regular, and the corresponding shape can be processed on the copper substrate with a press head. Step 3) Select alloy powder as the substrate because a layer of doped diamond has been deposited on the single-side surface of the diamond particles, and the surface is irregular, and it is impossible to use a press head to process a shape that matches the diamond surface.
[0017] Preferably, in step 4), the temperature for etching the exposed diamond with hydrogen is 700-1000° C., and the etching time is 5-60 minutes.
[0018] Preferably, in steps 2) and 4), the thickness of the pulsed deposited doped diamond layer is 2000-3000 nm, and the doping elements are boron-nitrogen co-doping or boron-argon co-doping. The above doping elements are commonly used in the field of diamond doping and can increase the hardness of diamond.
[0019] Preferably, in steps 2) and 4), the conditions for pulsed deposition of doped diamond are: hydrogen flow rate of 300 sccm, methane flow rate of 10-40 sccm, argon flow rate of 6-40 sccm, trimethylboron (B(CH3)3) flow rate of 0-3 sccm, nitrogen flow rate of 1-20 sccm, and the gas flow rate can be adjusted by a flow valve to control the amount of doping gas added, that is, different doping gases are introduced in a pulsed manner. The diamond growth temperature is 800-1000 °C, the power range is 4000-7000 W, the chamber pressure is 10-25 kPa, and the pulsed deposition single layer deposition thickness is 50-300 nm.
[0020] The invention also provides diamond particles with a deposition layer prepared by the method.
[0021] Preferably, in step 5), the particle size of the diamond particles in the deposited layer obtained is less than 15 μm. The diamond particles prepared by the above method have a multilayer structure, that is, pulsed deposition of doped diamonds enveloping undoped diamond particles forms a multilayer structure of doped diamonds. This structure increases the hardness of the diamond particles by 2 to 4.5 times.
[0022] The technical principle of the present invention is as follows:
[0023] The present invention improves the hardness of diamond particles by mosaic splicing. The method processes micropores on the surface of the substrate, and the micropores ensure that about half of the diamond particles are exposed. The undoped single crystal diamond is spliced into the micropores of the copper substrate to form an alloy substrate embedded with diamond particles, and the doped diamond is pulse-deposited on the surface of the undoped diamond particles. After the deposition is completed, the diamond particles that are connected to the film are removed and inverted on the alloy powder, so that the diamond and the alloy powder are combined to prepare a substrate wrapped with a diamond doped surface, and the substrate is placed in a CVD device. Hydrogen is first introduced to etch the exposed diamond particles, and then the doped diamond of the same thickness is pulse-deposited again, and then the diamond film connected to the sheet is acid-etched, and the metal residue on the surface of the diamond film is removed and the diamond film is crushed to form diamond particles with a multilayer structure. The method not only significantly improves the hardness and uniformity of the diamond particles, but also simplifies the process flow, reduces the production cost, has a wide range of industrial application prospects, and is particularly suitable for the manufacture of high-precision cutting, grinding and polishing tools.
[0024] The advantages of the present invention are as follows:
[0025] (1) The present invention adopts mosaic splicing technology, which has a simple process flow, is easy to operate, is suitable for large-scale production, and reduces manufacturing complexity and time cost.
[0026] (2) Through process design, a substrate that wraps part of the diamond particles is prepared, which increases the contact area between the diamond and the substrate. During the deposition process, the graphitization damage of the undoped diamond particles caused by high temperature due to high power can be effectively prevented, the power and deposition rate of the CVD equipment can be increased, the heat dissipation efficiency can be improved, and the integrity and performance of the diamond particles can be guaranteed.
[0027] (3) The present invention introduces doping gas in a pulsed manner, and sequentially deposits doped diamond on the surface of diamond particles in a pulsed manner, thereby preparing diamond with a multi-layer doping structure and obtaining diamond particles with ultra-high hardness. The multi-layer doping structure contains high-density twins and stacking faults, thereby achieving enhanced hardness of diamond.
[0028] (4) By combining diamond with alloy powder to prepare a secondary deposition substrate, the substrate tightly wraps the diamond to increase the contact area, improve the heat dissipation efficiency, and solve the heat dissipation problem of secondary pulse deposition pulse-doped diamond. If an ordinary substrate is used, there will be a gap between the diamond and the substrate, and untimely heat dissipation will lead to graphitization damage of the diamond film.
[0029] (5) The bare diamond particles are etched by hydrogen etching technology to prevent graphitization damage of the diamond particles during the vacuum hot melting process and ensure the performance of the final sample.
[0030] (6) The final diamond particle size can be controlled within a smaller range through crushing to meet high precision requirements. The present invention can improve the grade of diamond powder through this method. The prepared high-hardness diamond particles significantly improve the cutting efficiency and service life of diamond wire saws and rope saws, and are suitable for high-precision cutting and processing applications, meeting the industry's demand for high-performance cutting tools. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 A process flow chart of the method for improving the hardness of diamond particles by mosaic splicing provided by the present invention;
[0033] Figure 2 A schematic diagram of the structure of a diamond with a deposited layer obtained by the present invention;
[0034] Among them, 1-CVD pulsed deposition of doped diamond layer, 2-undoped diamond particles;
[0035] Figure 3 The figure shows the hardness improvement factor of different samples using the method of the present invention.
[0036] Figure 4 The Raman surface scanning data of multi-layer diamond particles prepared by the method of the present invention. DETAILED DESCRIPTION
[0037] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0038] Figure 1The process flow chart of the method for improving the hardness of diamond particles by mosaic splicing provided by the present invention. It includes processing micropores into a copper substrate, splicing undoped single crystal diamond particles onto the copper substrate, and partially embedding the diamond particles into the copper substrate. Pulse-depositing a doped diamond layer on the surface of the diamond particles by CVD technology. Diamond is combined with alloy powder, and a secondary deposition substrate is prepared by vacuum hot melting technology. After etching the exposed diamond particles on the secondary deposition substrate, doped diamond is pulse-deposited again, and finally the connected diamond film is acid-etched, and the metal residue on the surface of the diamond film is removed and then the diamond film is crushed to finally obtain superhard diamond particles with a multilayer structure.
[0039] Figure 2 The structure diagram of the diamond with deposition layer obtained by the present invention is as follows. The hardness of the diamond particles can be significantly improved by coating the surface of the undoped diamond particles 2 with multiple layers of CVD pulsed deposition doped diamond layers 1.
[0040] Figure 3 The hardness of the samples obtained after different diamond particles were prepared by the method of Example 1, and the hardness improvement multiple. After the four samples with different initial hardness were improved by the method of the present invention, the hardness of the samples was increased to more than 170 GPa. This shows that the method can effectively improve the hardness of diamond particles, and diamond particles with different initial hardness can be increased to more than 170 GPa, and the hardness is increased by about 2 to 4.5 times according to the initial hardness.
[0041] Figure 4 This is the Raman surface scanning data of the sample prepared in Example 1. Through the Raman surface scanning, it can be seen that the undoped diamond particles are wrapped by the pulsed doping layer. The pulsed doping layer has a multi-layer structure and can significantly improve the hardness of the diamond particles.
[0042] Example 1
[0043] This embodiment introduces a method for improving the hardness of diamond particles by mosaic splicing technology. First, undoped single-crystal diamond particles of about 5 μm are selected, and then a pressure head of equivalent size is selected to process regularly arranged micropores on a copper substrate, and then the single-crystal diamond particles are spliced onto the copper substrate. Subsequently, the substrate with single-crystal diamond particles spliced on the surface is placed in an MPCVD device, and 300 sccm ultrapure hydrogen and 15 sccm methane are introduced. Argon and nitrogen are introduced in a pulsed manner under the conditions of a deposition temperature of 850 °C, a microwave power of 6000 W, and a cavity pressure of 12 kPa. The argon flow rate is 10-20 sccm, and the nitrogen flow rate is 5-15 sccm. The gas flow rate is adjusted by controlling the flow valve to achieve different doping effects. The doped diamond layer is pulsed deposited on the surface of the diamond particles, with a single layer deposition thickness of 100 nm and a deposition time of 6 hours. The particles with deposited doped diamond layer were removed from the substrate and placed on the copper-nickel alloy powder with the doped surface facing down. The particles were heated at 1000 °C for 5 minutes in a vacuum environment using a vacuum hot melt device to prepare an alloy substrate wrapped with diamond doped surface. After cooling, the particles were placed in the MPCVD device again, and 300 sccm of ultrapure hydrogen was introduced at 900 °C to etch the diamond particles for 30 minutes. The same deposition conditions were then repeated to pulse-deposit the doped diamond layer on the other side of the diamond particles. Finally, the deposited diamond film was acid-etched, and the metal residue on the surface of the diamond film was removed and then the diamond film was crushed to obtain multilayer superhard diamond particles with a hardness increase of 2 to 4.5 times. The diamond particles prepared by this method have significant advantages in hardness and uniformity, and are suitable for the manufacture of high-precision cutting, grinding and polishing tools.
[0044] Example 2
[0045] This embodiment introduces a method for improving the hardness of diamond particles by mosaic splicing technology. First, undoped single-crystal diamond particles of about 5 μm are selected, and then a pressure head of equivalent size is selected to process regularly arranged micropores on a copper substrate, and then the single-crystal diamond particles are spliced onto the copper substrate. Subsequently, the substrate with single-crystal diamond particles spliced on the surface is placed in an MPCVD device, and 300 sccm of ultrapure hydrogen is first introduced, 900 ° C, and etching is performed for 30 minutes. Then 20 sccm of methane is introduced, and under the conditions of deposition temperature of 900 ° C, microwave power of 6000 W, and cavity pressure of 15 kPa, trimethyl boron (B(CH3)3) 0~0.2 sccm, argon 5~10 sccm, and trimethyl boron and argon are introduced in a pulsed manner. The gas flow rate is adjusted by controlling the flow valve to achieve different doping effects. The doped diamond layer is pulsed deposited on the surface of the diamond particles, with a single layer deposition thickness of 200nm and deposition for 3 hours. The particles with deposited doped diamond layer were removed from the substrate and placed with the doped surface facing down on the copper-nickel alloy powder. The particles were heated at 1000 °C for 5 minutes in a vacuum environment using a vacuum hot melt device to prepare an alloy substrate wrapped with diamond doped surface. After cooling, the particles were placed in the MPCVD device again, and 300 sccm of ultrapure hydrogen was introduced at 900 °C to etch the diamond particles for 30 minutes. The same deposition conditions were then repeated to pulse-deposit the doped diamond layer on the other side of the diamond particles. Finally, the deposited diamond film was acid-etched, and the metal residue on the surface of the diamond film was removed and then the diamond film was crushed to obtain multilayer superhard diamond particles with a hardness increase of 2 to 4.5 times. The diamond particles prepared by this method have significant advantages in hardness and uniformity, and are suitable for the manufacture of high-precision cutting, grinding and polishing tools.
[0046] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for increasing the hardness of diamond particles by mosaic splicing, characterized in that: The method comprises the following steps: 1) Substrate preparation: Select the single crystal diamond particles to be processed, measure the particle size of the diamond particles, and then use an indenter with a size comparable to that of the diamond particles to machine fixedly arranged micropores on the surface of the copper substrate; 2) First pulse deposition after splicing diamond particles: Splice single crystal diamond into micro-holes processed on the copper substrate, put the copper substrate with spliced diamond particles into the CVD equipment, introduce different doping gases in a pulsed manner, and pulse-deposit a layer of doped diamond on the surface of the exposed diamond particles, and connect the diamond particles to form a film through the deposited layer; 3) Preparation of secondary deposition substrate: The film formed by the particles of the pulsed deposition doped diamond layer is removed and placed upside down on the alloy powder to combine the diamond sheet with the alloy powder to form an alloy substrate covering the diamond doped surface; 4) Pulse deposition again: Place the above substrate in the CVD equipment, first introduce hydrogen to etch the diamond particles, and then pulse-deposit doped diamond on the surface of the diamond particles until the thickness reaches the thickness of the first pulse deposition; 5) Crushing treatment: The diamond particles that have been connected to form a diamond film after deposition are acid-etched, and the diamond film is crushed after the metal residue on the surface of the diamond film is removed to obtain diamond particles with a deposition layer.
2. The method for increasing the hardness of diamond particles by mosaic splicing according to claim 1, characterized in that: In step 1), single crystal diamond particles are spliced into the processed copper substrate micropores, and the micropore circumference spacing is less than twice the thickness of the pulsed deposited doping layer.
3. The method for increasing the hardness of diamond particles by mosaic splicing according to claim 2, characterized in that: In step 1), the size of the undoped diamond particles is micrometer level.
4. The method for increasing the hardness of diamond particles by mosaic splicing according to claim 3, characterized in that: In step 1), the particle size of the undoped diamond particles is 4-8 μm, the maximum width of the microholes processed on the substrate is 4-8 μm, the hole depth is 2-4 μm, and the spacing between the microholes is less than 3 μm.
5. The method for increasing the hardness of diamond particles by mosaic splicing according to claim 1, characterized in that: In step 3), the alloy powder for preparing the secondary deposition substrate is selected from one of titanium-based alloy, nickel-based alloy and copper-based alloy, and the process for preparing the secondary deposition substrate is vacuum hot melting.
6. The method for increasing the hardness of diamond particles by mosaic splicing according to claim 1, characterized in that: In step 4), the temperature of introducing hydrogen to etch the exposed diamond is 700-1000°C, and the etching time is 5-60 minutes.
7. The method for increasing the hardness of diamond particles by mosaic splicing according to claim 1, characterized in that: In steps 2) and 4), the thickness of the pulsed deposited doped diamond layer is 2000-3000 nm, and the doping elements are boron-nitrogen co-doping or boron-argon co-doping.
8. The method for increasing the hardness of diamond particles by mosaic splicing according to claim 7, characterized in that: In steps 2) and 4), the conditions for pulsed deposition of doped diamond are: hydrogen flow rate of 300 sccm, methane flow rate of 10~40 sccm, argon flow rate of 6~40 sccm, trimethyl boron flow rate of 0~3 sccm, nitrogen flow rate of 1~20 sccm, and different doping gases are introduced in a pulsed manner.
9. The method for increasing the hardness of diamond particles by mosaic splicing according to claim 8, characterized in that: In steps 2) and 4), the diamond growth temperature is 800~1000 °C, the power range is 4000~7000 W, the chamber pressure is 10~25 kPa, and the pulsed deposition single layer deposition thickness is 50~300 nm.
10. Diamond particles having a pulsed deposition layer prepared by the method of claims 1 to 9.
Citation Information
Patent Citations
Deposition substrate for single crystal diamond growth and method for producing single crystal diamond
CN114182342A
Method for synthesizing large-size diamond crystal by using chemical vapor deposition method
CN116334752A
Method for preparing hexagonal boron nitride film by microwave plasma chemical vapor deposition system
CN116356280A
Porous boron-doped diamond composite film temperature sensor and preparation method thereof
CN118603345A
Variable-temperature vapor deposition process
WO2024138229A1